Normative Versus Positive Approach to Fiscal Decentralisation and the Measures of Decentralisation. An Analysis based on the Example of Selected Countries of Central and Eastern Europe - Guziejewska, Beata (Comparative Economic Research. Central and Eastern Europe, 2018)
This article deals with the problem of a discrepancy between the recommendations of the theory of public finance, in its various trends, and decentralisation processes in practice. The analysis is both theoretical and empirical. The aim of the discussion is to present the theoretical findings regarding fiscal decentralisation as well as to compare them with the recommendations of the fiscal decentralisation doctrine and with the trends in the practice of local government finances in Poland and selected countries of Central and Eastern Europe. The literature on the subject, studies by international institutions, as well as data from Eurostat and the European Commission are used in the deliberations. Two groups of countries were subject to a comparative analysis: the Visegrad Group Countries and the three Baltic states. These countries differ significantly in the scope of their fiscal decentralisation. Latvia, the Czech Republic and Poland seem to be most advanced in the process. In the conclusion of the study, a recommendation for a wider use of property taxes and the so‑called ‘additions to state taxes’ is put forward.